A gamma-ray dose rate assessment method for arbitrary shape geometries based on voxelization algorithm. (May 2019) - Yang, Li-qun; Liu, Yong-kuo; Peng, Min-jun; Li, Meng-kun
Abstract: A gamma-ray dose rate assessment method for arbitrary shape sources and arbitrary shape shields is proposed in this paper. The method is based on voxelization algorithm and Point-Kernel method. Using the modeling capabilities of 3dsMax software, the method can visually perform geometric modeling for arbitrary shape three-dimensional (3D) geometries without writing the textual description. The 3D geometry is imported as a 3DS format file. Using the voxelization-based modeling method, the arbitrary shape solid models are automatically converted to voxel models. In the point-kernel calculation process, source voxels are used as point kernels, and shielding voxels are used to calculate mean free paths (mfp). The effectiveness and flexibility of the proposed method were verified by simulating arbitrary shape geometries, and the accuracy was proved by comparing with MCNP code. The proposed method is suitable for calculating dose rate of arbitrary shape geometries after cutting and demolition operations during the decommissioning of nuclear facilities. Highlights: The method calculates gamma-ray dose rate of arbitrary geometries. The arbitrary shape solid models are automatically converted to voxel models. Source voxels are used as point kernels in the point-kernel calculation.